2013
DOI: 10.1371/journal.pone.0055695
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Cigarette Smoke (CS)-Induced Autophagy by Nrf2

Abstract: Cigarette smoke (CS) has been reported to induce autophagy in airway epithelial cells. The subsequent autophagic cell death has been proposed to play an important pathogenic role in chronic obstructive pulmonary disease (COPD); however, the underlying molecular mechanism is not entirely clear. Using CS extract (CSE) as a surrogate for CS, we found that it markedly increased the expressions of both LC3B-I and LC3B-II as well as autophagosomes in airway epithelial cells. This is in contrast to the common autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 57 publications
4
35
1
1
Order By: Relevance
“…HDAC6 expression was consistently elevated in Nrf2 -/-mice tissues and cells, which also displayed increased protein ubiquitination. Interestingly, NRF2 inhibition increases autophagy (71), and increasing NRF2 represses CSEinduced autophagosome formation (72). These results suggest that HDAC6 expression is increased by oxidative and proteostatic stress and may be counterregulated by NRF2.…”
Section: Figure 10mentioning
confidence: 87%
“…HDAC6 expression was consistently elevated in Nrf2 -/-mice tissues and cells, which also displayed increased protein ubiquitination. Interestingly, NRF2 inhibition increases autophagy (71), and increasing NRF2 represses CSEinduced autophagosome formation (72). These results suggest that HDAC6 expression is increased by oxidative and proteostatic stress and may be counterregulated by NRF2.…”
Section: Figure 10mentioning
confidence: 87%
“…The observed mortality of 16HBE cells after CSE exposure, that has been observed also in other cell types [43], could be due to a different form of cell death, i.e. an autophagic cell death, whose morphological and biomedical features are distinct from other cell death pathways [44] and that has been demonstrated to be induced by cigarette smoke in airway epithelial cells [45]. Glutathione is the most abundant intracellular antioxidant thiol and is essential to redox protection during oxidative stress.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 89%
“…Nrf2 appears to be involved in the regulation of protein aggregation in autophagic substrate selection (43) as well as autophagy per se (44)(45)(46)(47). Although it remains unclear whether the observed increased steady state levels of autophagosomes in Nrf2-deficient breast cancer cells, endothelial cells, and airway epithelial cells are caused by an impairment of autophagosome clearance (44,46,47), it has been demonstrated that Nrf2 is a critical mediator of autophagic clearance of ubiquitinated protein aggregates in macrophages (45).…”
Section: Nrf2 In Autophagymentioning
confidence: 99%
“…Although it remains unclear whether the observed increased steady state levels of autophagosomes in Nrf2-deficient breast cancer cells, endothelial cells, and airway epithelial cells are caused by an impairment of autophagosome clearance (44,46,47), it has been demonstrated that Nrf2 is a critical mediator of autophagic clearance of ubiquitinated protein aggregates in macrophages (45). In addition, a recent study showed that Nrf2 is capable of clearing phosphorylated tau by induction of nuclear dot protein 52 (NDP52), an autophagy adaptor protein (also known as CALCOCO2) in the presence of autophagy stimulator thereby potentially contributing to brain protection (48).…”
Section: Nrf2 In Autophagymentioning
confidence: 99%